The lung and gut microbiome: what has to be taken into consideration for cystic fibrosis? - Héry-Arnaud, Geneviève; Boutin, Sébastien (Journal of cystic fibrosis, 2019)
The 15th European Cystic Fibrosis Society (ECFS) Basic Science pre-conference Symposium focused on the topic of the microbiome, asking the question “The lung and gut microbiome: what has to be considered for cystic fibrosis (CF)?” This review gives an overview of the main points raised during the symposium, which dealt with the technical considerations, pathophysiology and clinical implications of the microbiome in CF.
Available online 25 November 2018
Gesehen am 19.11.2019